Government Communication Strategies in Time of Pandemic: Comparative Study between South Korea and Indonesia - Badrul Arifin (Policy & Governance Review, 2022)
The COVID-19 pandemic is a multi-faceted crisis with a very high public health risk. The more difficult the pandemic, the greater emphasis must be placed on effective government communications. It will play a major role in responding to the pandemic successfully. Meanwhile, ineffective government communication has resulted in widespread public uncertainty and major blunders in reacting to escalating health dangers have had potentially devastating health and social consequences for society, as well as protracted the outbreak. This paper conducts an empirical and comparative analysis of the determinants of government communication strategies in responding to the COVID-19 pandemic in Korea and Indonesia. It aims to explain the success of Korean public communication compared to Indonesia. This study uses a literature review along with a case study using comparable variables. The determining factors used are initial conditions, institutional capacity, transparency, effective coordination, and collaboration between stakeholders. Evidence shows that Korea is better off across all determinants. The lessons from the experience of government communication strategies in responding to the pandemic in these two countries can be used to teach other countries what to do and not to do in government communication services in the midst of a pandemic situation.